2018
DOI: 10.1155/2018/6080432
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Ag-TiO2 Composites Deposited by Photoreduction under UV Irradiation

Abstract: In this work, we synthesized Ag nanoparticles on TiO2 thin films deposited on soda lime glass substrates. Ag nanoparticles were synthesized by photoreduction under UV irradiation silver nitrate solution. X-ray diffraction, Raman spectroscopy, scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) measurements were used for physicochemical characterization. The structural study showed that all samples were polycrystalline, main phases were anatase and rutile, and no additional signals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Moreover, the 5.8 eV splitting between binding energies confirms the presence of Ti 4+ in the photocatalyst. This finding is consistent with previous research 38 . The high‐resolution Ag 3d spectrum (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the 5.8 eV splitting between binding energies confirms the presence of Ti 4+ in the photocatalyst. This finding is consistent with previous research 38 . The high‐resolution Ag 3d spectrum (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, improving the photoresponse of ZnO to longer wavelengths of the electromagnetic spectrum is the goal to be achieved for photocatalytic applications under solar irradiation [7]. Different strategies have been reported to extend photoresponse of semiconductors into the visible light region: (a) sensitization with natural and synthetic dyes [8][9][10][11], (b) coupled semiconductors [12][13][14], (c) surface plasmon resonance [15][16][17][18], and (d) doping ZnO structure with metals and nonmetals [19][20][21]. Among these, the doping process can modify the band gap of ZnO, generating electronic state intragap inside of the semiconductor thus ensuring the photoactivity redshift; on that topic, different authors have reported that ZnO changed photoresponse after the doping process [22].…”
Section: Introductionmentioning
confidence: 99%
“…The Modeling and Application of Advanced Oxidation Processes (MAOX) Group (Universidad de Cartagena 2010) was the pioneer in this field, with a study where they developed a mathematical model that allows to simulate the reflection of direct solar radiation in a CPC and calculated the involute length of the collector. This mathematical model was the first approach to radiation absorption models that involve solar radiation for photochemical or photothermal applications [109] . Later, this group would model the pilot scale photocatalytic degradation of 4‐chlorophenol, DCA and phenol in three CPC reactors that included the estimation of scattering‐absorption of the UV photons and the formulation of a generalized kinetic law with predictive quantum yields [110] .…”
Section: The Presentmentioning
confidence: 99%
“…This mathematical model was the first approach to radiation absorption models that involve solar radiation for photochemical or photothermal applications. [109] Later, this group would model the pilot scale photocatalytic degradation of 4-chlorophenol, DCA and phenol in three CPC reactors that included the estimation of scattering-absorption of the UV photons and the formulation of a generalized kinetic law with predictive quantum yields. [110] Subsequent studies would focus on the photoreactors design and their applicability for emergent pollutants removal in water.…”
Section: The Presentmentioning
confidence: 99%